Structure of non-maximally decimated filter bank derived by MSFGs - Wang, Luyun (2018)
Practical applications in digital communication need non-maximally decimated filter banks to provide oversampled baseband signals for other necessary operations. The non-maximally decimated filter banks allow the required prototype filter to have wider transitional band to significantly reduce the required computational complexity. This Letter presents a non-maximally decimated filter bank structure derived by using multi-rate signal flow graphs.